The effectiveness of digital storytelling as a tool for the formation of administrative values of students in pedagogical practice - Al-Awamrah, Abdelsalam Fahad; Bani-Khair, Baker Mohammad Jamil; Kaddum, Mahmud; Rababah, Luqman M.; Al-Habies, Feras Ali Mohammad; Wolor, Christian Wiradendi; Rababah, Mahmoud Ali Ibrahim (Russian State Vocational Pedagogical University, 2026)
Introduction. Digital storytelling is a crucial component of contemporary value-oriented education. Complementing traditional teaching methods, it serves as a tool to shape and convey administrative values such as justice, equality, and responsibility. Aim. The present research aims to examine teachers’ attitudes towards the use of digital storytelling in developing administrative values. Methodology and research methods. The research employed descriptive and analytical methods. The general population comprised a random sample of 466 secondary school teachers in Irbid, Jordan. Data were collected using specialised survey instruments. Results. The data obtained indicate a high level of approval for the use of the digital storytelling method among the respondents, as confirmed by average rating values ranging from 4.16 to 4.23 on a closed scale. Scientific novelty. The scientific novelty of this study lies in its focus on the underexplored issue of utilising digital storytelling to develop administrative values within the framework of the Jordanian national education system. Practical significance. The results of this research may be highly sought after when designing advanced training programmes for teachers aimed at developing competencies in the effective use of digital storytelling methods. They are also valuable for informing educational policy principles focused on integrating digital technologies and narrative practices into curricula. © Al-Awamrah A.F., Bani-Khair B.M., Kaddum M., Rababah L.M., Al-Habies F.A.M., Wolor C.W., Rababah M.A.I.
Keywords: administrative values; digital storytelling; Jordanian school teachers; value-oriented education